THE Agadir Port And Digues Protection : What is the best protection of a port? (International Journal of Scientific Research and Management (IJSRM), 2018)
At all times, the man wanted to tame the surrounding elements, first by pride and curiosity and then by security measures because they threaten his own existence, and to do so, it was essential to understand how these phenomena occur, then to develop strategies, protectors, or build megastructures; for example, it was imperative to explore deeply the nature of waves and currents in order to build dikes, or even take advantage of this abundance of inexhaustible energy (tidal power). Thus, it is proposed to cover this vast field of applications that is the swell on the harbor dike.